Biology Teacher Creativity at SMKN Maros Regency in Solving Online Learning Problems by Utilizing E-Learning - Pertiwi Indah Lestari; Rizki Amalia Nur; Rika Riyanti (Biosfer: Jurnal Tadris Biologi, 2022)
This study employed a qualitative method to determine the teachers’ creativity in utilizing e-learning media in online learning. This study implemented a survey approach that involved theories, relevant evidence, and existing facts by emphasizing the structural model (path) of the relationship between the variables studied. The subjects of this study were 20 students of SMKN 2 Maros and four homeroom teachers. The data collecting technique used by the researchers were questionnaires and online interviews. The data analysis technique referred to by Miles and Huberman, namely data reduction, data display, and conclusion drawing/verification. Based on research, the teachers' creativity at SMKN 2 Maros in utilizing e-Learning was 82.5 and 85 in the high creativity category. Therefore, the creativity in using e-Learning during the online learning process was high.